Bird diversity in Ake Jawi Village, Aketajawe Lolobata National Park, Halmahera, North Maluku - Ramadani, Annisa; Assalam, Muhammad Hudan; Satrio, Muhammad Bagus; Nurhasanah, Annisa Haryanti; Setia, Tatang Mitra (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
Aketajawe Lolobata National Park is an area in the Wallacea area with ​​167,319.32 hectares. The TNAL area has 108 buffer villages, one of which is a bird-friendly village in Ake Jawi Village. This study aims to determine the types of birds, analyze diversity, dominance, and types of bird feed. Data collection used the available paths using the visual encounter survey (VES) method. The results of this study managed to identify as many 31 bird species grouped into 23 family and 31 genus, 15 of them are Indonesian endemics, and 12 species are endemics to North Maluku. Based on the Shannon-Wiener diversity index, Ake Jawi Village belongs to the medium category, with an index value of 2.889, and the dominance category 0.098 based on the index low. The percentage of encounters with insect-eating birds (insectivores) such as the cow swiftlet, cotton-halmahera, and goliath lathe reached 39%, followed by frugivores such as the papuan hornbill, white cockatoo, and gray-headed walik by 36%.